Reversible phosphorescence in pseudopolyrotaxane elastomer - Cui, Fengyao; Zhang, Qiaona; Xiao, Tangxin; Wang, Zhouyu; Wang, Leyong (Chinese chemical letters, 2024)
[Display omitted] While polyrotaxanes have found applications in the construction of diverse soft materials, there is a limited exploration on mechanical force-responsive phosphorescence emission systems. Recently, Yong Chen, Yu Liu, and co-workers from Nankai University have addressed this gap by developing a novel type of supramolecular elastomer exhibiting reversible phosphorescent behavior. This innovative material displays stretch-induced phosphorescence enhancement and has been successfully employed for information storage and encryption in specialized environments.